Efficacy of a Vancomycin/Tobramycin-Doped Polyvinyl Alcohol (PVA)- Polymeric Dicalcium Phosphate Dehydrate (P-DCPD) Composite for Prevention of Periprosthetic Infection in a Mouse Pouch Infection Model Implanted with 3D-printed Porous Titanium Cylinders - Dubé, Michael; Miller, Adam; Kaminski, Michael; Bou-Akl, Therese; Pawlitz, Paula; Ren, Weiping; Markel, David C. (Archives of Clinical and Biomedical Research, 2026)
Prosthetic joint infection (PJI) is a challenging problem with current techniques including irrigation and antibiotics having limited effectiveness. This study evaluated the effect of antibiotic doped polyvinyl alcohol (PVA)- polymeric dicalcium phosphate dehydrate (P-DCPD) composite on prevention of PJI in a mouse pouch model implanted with porous titanium (Ti) cylinders. Air pouches were created in 30 mice (n=10 within each group). Pouches were implanted with either porous Ti cylinders only (negative control), Ti cylinders and Staphylococcus aureus (S. aureus) (positive control), or Ti cylinders pre-doped with antibiotic-loaded PVA-P-DCPD and S. aureus (treatment group). At sacrifice, mouse washings and Ti cylinders were collected for bacterial analysis. There were no detectable bacteria in the washings or cylinder sonicate following implantation with antibiotic doped PVA-PDCPD or in the negative controls. Bacteria were present in the washings of the positive control (1894 ± 2455 cfu/ml) which was significant compared to the treatment group (P< 0.001). Similarly, Ti discs had significantly lower bacterial counts in the treatment group when compared to positive controls (0 cfu/ml vs 22233 ± 33735 cfu/ml, P=0.002). Pre-treatment of titanium implants with Vancomycin and Tobramycin doped PVA-P-DCPD led to a significant reduction in bacterial load which may represent an effective means of preventing PJI in the future.